A stationary, variable DOF flight control system for an unmanned quadrocopter - Omurlu, Vasfi Emre; Kirli, Ahmet; Buyuksahin, Utku; Engin, Seref Naci; Kurtoglu, Sedat (Tubitak Scientific & Technological Research Council Turkey, 2011)
Unmanned, air vehicles ( UAV) and especially quadrocopters have drawn, great attention in recent years because of their maneuverability and nonlinear control problem. Most of the related research concentrate on control; yet, design and communication are also some sub-topics. In this paper, a stationary, four rotor air vehicle with limited/controlled degree of freedom is constructed so that various control algorithms and their changing effects with varying vehicle dynamics can be studied on the ground for safety purposes. Ascending/descending, pitch/yaw/roll motions can be limited by setting the vehicle's degree of freedom mechanically, resulting better net observability of the control algorithms on the vehicle's dynamic performance. Design, in terms of mechanics, mechatronics and software are presented and the usability of the system is shown by comparing simulation and mal system, responses utilizing preliminary control trials.
Keywords: Quadrocopter; UAV; mechatronics; stationary testbed; STABILIZATION; QUADROTOR; Computer Science; Engineering